Comparison of Clinical Outcomes between the Right and Left Radial Artery Approaches from the Korean Transradial Coronary Intervention Registry - Park, Ji Young; Rha, Seung-Woon; Choi, Byong Geol; Oh, Dong Ju; Choi, Cheol Ung; Youn, Young-Jin; Yoon, Junghan (Yonsei medical journal, 2017)
Transradial intervention (TRI) shows anatomical and technical differences between the right radial approach (RRA) and left radial approach (LRA). The aim of this study was to evaluate the efficacy and safety using LRA, compared with RRA. A total of 1653 consecutive patients who underwent TRI from November 2004 to October 2010 were enrolled in the Korean multicenter TRI registry. The patients were divided into two groups: the RRA group (n=792 patients) and the LRA group (n=861 patients). To adjust for any potential confounders, propensity score matched (PSM) analysis was performed (C-statistic: 0.726). After PSM, a total of 1100 patients were enrolled for analysis. After PSM, the RRA group exhibited a larger contrast volume (259.3±119.6 mL vs. 227.0±90.7 mL, p<0.001), a longer fluoroscopic time (22.5±28.0 minutes vs. 17.1±12.6 minutes) and higher access site change (12.3% vs. 1.0%, p<0.001) than the LRA group. Meanwhile, the LRA group showed a shorter procedure time (49.2±30.4 minutes vs. 55.4±28.7 minutes, p=0.003) than the RRA group. After PSM, in-hospital complications and 12-month cumulative clinical outcomes were similar between the two groups. Of the two TRI methods, LRA was associated with better procedural efficacy, including shorter procedural time, smaller contrast volume, and less access site change than RRA. However, both methods showed similar 12-month cumulative clinical outcomes. Therefore, LRA was deemed superior to RRA in terms of procedural feasibility without a significant difference in clinical outcomes.